Communicative paradigm in the research of joint stock companies financial security - STASHCHUK, Olena (Scientific journal «World of Finance», 2019)
Introduction. The development of the information society requires the application of the bases of the communicative approach in the process of researching the financial security of joint stock companies. This is due to the high level of sensitivity of corporate structures to the quality, completeness and timeliness of financial information and, as a consequence, can lead to a decrease in the efficiency of financial and economic activity of joint stock companies and the level of their financial security. The purposeof the article is to outline the place of the communicative paradigm in the scientific knowledge of the financial security of joint stock companies, to identify its main characteristics. On this basis, there is a need for structuring financial communications of the financial security system of joint stock companies. Results. The results of the study allowed to establish such basic essential characteristics of the communicative paradigm in the study of financial security of joint stock companies, such as multisubjectivity, multilevelness, intersubjectivity, equality of control subjects, flexibility and dynamism of the structure of the subject of management. It is established that in the structure of financial communications of the financial security system of joint stock companies are allocated intangible, basic and derivative. The author’s approach to understanding the methodology of scientific knowledge of financial security of joint stock companies as an interconnection of financial resources of corporate structures and the formation of relevant financial information with the aim of regulating the interests and intentions of all stakeholders is proposed. Conclusions. Construction of the methodology of scientific knowledge of financial safety of joint stock companies on the basis of the above mentioned methodological approaches can contribute to the formation of a real assessment of the latest trends in the formation of financial security of joint stock companies, the identification of weaknesses and the risks of their mplementation in the context of existing macroeconomic and microeconomic threats, as well as substantiation of effective directions for increasing financial security. We believe that the application of such scientific approaches to the study of financial security of joint stock companies will also enhance the quality of the use of mathematical tools in financial science, a more detailed study of the basic models of the functioning of the finances of joint stock companies, the accumulation of empirical data.